UJI ORGANOLEPTIK DAN ANALISA USAHA BAKSO SAPI DENGAN KONSENTRASI TEPUNG TAPIOKA YANG BERBEDA - Yannuarsita, Deni; Rintania, Sandris; Sasmito, Moch. Shandy (Universitas Muara Bungo, 2023)
The aims of This research are determining the percentage of tapioca flour that used in making meatballs for organoleptic tests which include of color, flavor, taste and texture as well as to determine the business analysis to know that is worth to developing or not. This research was carried out from June 20 2023 to August 10 2023 at the State Polytechnic Banyuwangi Animal Products Processing Technology laboratory. This research used a Randomized Block Design (RAK) method, using 4 treatments and each treatment consisted of 5 replications, namely P0 = Meatballs with 10% tapioca flour concentration, P1 = Meatballs with 20% tapioca flour concentration, P2 = Meatballs with 30% tapioca flour concentration. P3 = Meatballs with 40% tapioca flour concentration. The data was analyzed using SPSS and continued with the DMRT test if there were significant differences, The result that in the color attribute there were significant differences between treatments, the highest mean value was in P2 3.87 ± 0.57 and the lowest was in P0 3.43 ± 0.63, while for the flavor, taste and Texture There is no significant influence of each treatment. From the overall analysis results it can be concluded that P2 is the best treatment. After analysis, it was found that the BEP price was IDR 9,000 and the BEP production was 27 packs, the R/C ratio was 1.39 and the ROI was 26. .65, from the results of the cost analysis it can be concluded that the meatball business is worth to developing.